2004
DOI: 10.1111/j.1469-7610.2004.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire for screening a broad range of DSM‐defined anxiety disorder symptoms in clinically referred children and adolescents

Abstract: The SCARED-R is a valuable addition to the arsenal of questionnaires that are used for the assessment of anxiety in youths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
2
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 27 publications
11
91
2
7
Order By: Relevance
“…Children are asked to score each of the 69 items on a three-point scale, where 0 = almost never, 1 = sometimes, and 2 = often. Adequate internal consistency, construct validity, and discriminant validity has been demonstrated in clinically anxious samples of youth as young as 8 years of age (Muris et al 2004;Muris and Steerneman 2001), and the measure has demonstrated sensitivity to treatment effects (Muris and Steerneman 2001). The Danish version of the questionnaire has also shown satisfactory psychometric properties (Esbjørn, Sømhovd, Caspersen, & Reinholdt-Dunne, 2012).…”
Section: Methodsmentioning
confidence: 94%
“…Children are asked to score each of the 69 items on a three-point scale, where 0 = almost never, 1 = sometimes, and 2 = often. Adequate internal consistency, construct validity, and discriminant validity has been demonstrated in clinically anxious samples of youth as young as 8 years of age (Muris et al 2004;Muris and Steerneman 2001), and the measure has demonstrated sensitivity to treatment effects (Muris and Steerneman 2001). The Danish version of the questionnaire has also shown satisfactory psychometric properties (Esbjørn, Sømhovd, Caspersen, & Reinholdt-Dunne, 2012).…”
Section: Methodsmentioning
confidence: 94%
“…Good internal consistency and construct validity are reported (e.g. Hale et al, 2005;Muris, Dreessen, Bögels, Weckx, & van Melick, 2004;Muris, Merckelbach, Ollendick, King, & Bogie, 2002).…”
Section: Methodsmentioning
confidence: 90%
“…Social anxiety for clinical pathology in this population of high students in a similar setting of 80% prevalence is not surprising since there are high levels of bullying in the same schools [12]. Utilising a questionnaire for screening a broad range of DSM-IV defined anxiety disorder symptoms in children and adolescents in the same setting, almost all students had separation anxiety, school phobia and obsessive or compulsive symptoms [12,[14][15]. The lowest anxiety symptoms (54.7%) were in specific phobia for animals [12].…”
Section: Anxiety Disorders In Childhood and Adolescentsmentioning
confidence: 91%